Quantification of DNA fragmentation in processed foods using real-time PCR. (1st July 2017) - Mano, Junichi; Nishitsuji, Yasuyuki; Kikuchi, Yosuke; Fukudome, Shin-ichi; Hayashida, Takuya; Kawakami, Hiroyuki; Kurimoto, Youichi; Noguchi, Akio; Kondo, Kazunari; Teshima, Reiko; Takabatake, Reona; Kitta, Kazumi
Highlights: A real-time PCR method to quantify the degree of DNA fragmentation was developed. An indicator value "DNA fragmentation index" was created to express the degree of DNA fragmentation. We demonstrated the efficacy of the method in quality control of PCR-based food analysis. Abstract: DNA analysis of processed foods is performed widely to detect various targets, such as genetically modified organisms (GMOs). Food processing often causes DNA fragmentation, which consequently affects the results of PCR analysis. In order to assess the effects of DNA fragmentation on the reliability of PCR analysis, we investigated a novel methodology to quantify the degree of DNA fragmentation. We designed four real-time PCR assays that amplified 18S ribosomal RNA gene sequences common to various plants at lengths of approximately 100, 200, 400, and 800 base pairs (bp). Then, we created an indicator value, "DNA fragmentation index (DFI)", which is calculated from the Cq values derived from the real-time PCR assays. Finally, we demonstrated the efficacy of this method for the quality control of GMO detection in processed foods by evaluating the relationship between the DFI and the limit of detection.